دراسة آثاريه فنية لمجموعة مقاصير نحاسية بوسط الدلتا غير منشورة وغير مسجلة - الجندي، محمود سعد (الجمعية العربية للحضارة والفنون الإسلامية, 2017)
Allocating a specialized artistic study for a rare collection of copper maqasir (compartments) in central Delta –to be published for the first time- is of vital importance since maqasirs are rarely found around the structures over the graves of pious men as compared to wooden maqasirs. The probable reason for their scarcity is that the raw material cannot be found easily, and are expensive. In addition, manufacturing maqasirs requires creative and skilful industrial ways and methods of implementation, so the names of creators and manufacturers are not known in the modern age. The importance of this group of copper maqasirs goes back to their fine art, and artistic decoration as their writings carry historical and artistic value; they vary among Qur’anic verses, poems, propaganda phrases, and foundational texts which include the names of the creators, the industrial centers, the signatures of the makers, and a record of the history of the different ways of creation. The latter includes calculating the sentences, Hijri and Gregorian calendar, Arabic letters, and numerical calculations. This collection of metal objects goes back to almost one period of time which dates to the first third of the fourth century A.H. / twentieth century A.D. This occurred in only one geographical area which is central Delta. Thus, the current study focuses on the development of one of the most important domains in applied arts, specifically, the metal artifacts industry at a specific period of time and space in order to shed light on the movement of art, and its development in the provinces of Egypt, particularly the central Delta region. These maqasirs are limited to the chronology of Maqsuret Sidi Abdul Aziz Al-Dereni at Deren Village, Nabarouh Center, at Dakahlia Governorate (1320 A.H./1902 A.D.), Maqsuret Sidi Salem Al-Bili Abu Ghannam at Babbila, Kafr El-Sheikh Governorate (1323 A.H./1905 A.D.), Maqsuret Sidi Abdullah bin Harith at Saft Al-Turab Village, Al-Mahalla Al-Kubra Center in Gharbia Governorate (1329A.H./1911 A.D.), Maqsuret Sidi Mohamed Abdel Rahim in Tanta, Gharbia Governorate (1339 A.H./1920 A.D.), and Maqsuret Sidi Ibrahim Al-Khawas at Samanod, Gharbia Governorate (early 14th century A.H./20th century A.D.); all of which are unregistered as Islamic monuments. The study adopts an inductive, descriptive approach through a field study which address the overall shape of the Maqsuret, its design, method of manufacturing, elements of decoration, and implementation methods. The study follows the comparative analytical method through sources and references. It also recommends the need to register these maqasirs as Islamic monuments to protect and keep them safe.
يعتبر إفراد دراسة فنية متخصصة لمجموعة نادرة من المقاصير النحاسية بمنطقة وسط الدلتا يتم دراستها ونشرها لأول مرة من الأهمية بمكان، نظراً لقلة أعداد هذا النوع من المقاصير حول التراكيب فوق قبور الأولياء، بل وندرتها إذا ما قورنت بالمقاصير الخشبية، وربما يرجع ذلك إلى ندرة المادة الخام وكلفتها الاقتصادية علاوة على ما تتطلبه طرق الصناعة وأساليب تنفيذ العناصر الزخرفية من دقة ومهارات خاصة، وربما يفسر ذلك قلة أعداد هذه المقاصير وندرة ما وصلنا من توقيعات وأسماء الصناع. وترجع أهمية هذه المجموعة من المقاصير النحاسية فضلاً عن دقة صناعتها وثراء زخارفها وأساليب صناعتها، أنها تضم كتابات على قدر كبير من الأهمية التاريخية والفنية، تنوعت ما بين كتابات قرآنية وجنزية وعبارات دعائية وأشعار ونصوص تأسيسية شملت أسماء منشئين ومراكز صناعية وتوقيعات صناع وتسجيل لتاريخ صناعتها بطرق مختلفة منها طريقة حساب الجمل والتقويم الهجري والتقويم الميلادي بالحروف العربية وبالأرقام الحسابية. وهذه المجموعة من التحف المعدنية إنما ترجع إلى فترة زمنية واحدة تقريباً (الثلث الأول من القرن الرابع عشر الهجري/ العشرين الميلادي)، وتنحصر بمنطقة جغرافية واحدة هي منطقة وسط الدلتا، حتى يتسنى لنا من خلال الدراسة الوقوف على تطور واحداً من أهم الفنون التطبيقية في مجال صناعة التحف المعدنية في فترة زمنية محددة ومكان محدد، بغية إلقاء الضوء على حركة الفنون وتطورها في أقاليم مصر وبخاصة منطقة وسط الدلتا. وهذه المقاصير على الترتيب التاريخى، مقصورة سيدي عبدالعزيز الدريني بقرية درين مركز نبروه بمحافظة الدقهلية (1320ه/1902م)، ومقصورة سيدي سالم البيلي أبو غنام ببيلا بمحافظة كفر الشيخ (1323ه/1905م)، ومقصورة سيدى عبدالله بن الحارث بقرية صفط تراب مركز المحلة الكبرى بمحافظة الغربية (1329ه/1911م)، ومقصورة سيدى محمد عبدالرحيم بطنطا بمحافظة الغربية (1339ه/1920م) ومقصورة سيدي إبراهيم الخواص بسمنود بمحافظة الغربية )أوائل ق 14ه20م(، وجميعها غير مسجلة في عداد الآثار الإسلامية. وقد اتبع البحث المنهج الوصفي الاستقرائي من خلال الدراسة الميدانية، تناولت الشكل العام للمقصورة وتصميمها وطريقة صناعتها وعناصرها الزخرفية وأساليب تنفيذها، واتبع المنهج التحليلي المقارن من خلال المصادر والمراجع، وقد أوصى البحث بضرورة تسجيل هذه المقاصير في عداد الآثار الإسلامية لحمايتها والحفاظ عليها.
Keywords: العناصر الزخرفية; فن أشغال المعادن; التحف المعدنية; المقاصير النحاسية